Desarrollo de una bebida funcional rica en antioxidantes a base de la flor de jamaica (Hibiscus sabdariffa), mortiño (Vaccinium meridionale) y sábila (Aloe vera) edulcorada con stevia (Stevia rebaudiana) - Agualongo Tenelema, Laura Judith (2024)
The purpose of this research entitled: “Development of a functional drink rich in antioxidants based on hibiscus flower (hibiscus sabdariffa), mortiño (vaccinium meridionale) and aloe vera (Aloe vera) sweetened with stevia (stevia rebaudiana)”, was intended to contribute a new alternative in obtaining a drink with a high content of antioxidants and nutrients beneficial to health. DBCA was used, obtaining 4 treatments with 2 replicates each, treatment T1 was 40% hibiscus flower + 30% mortiño + 30% aloe vera, treatment T2 was 35% hibiscus flower + 25% mortiño + 40% aloe vera, Treatment T3 was 30% hibiscus flower + 20% mortiño + 50% aloe vera and treatment T4 was 25% hibiscus flower + 15% mortiño + 60% aloe vera. As a first objective, the analysis of the antioxidant activity was carried out under the (ABTS) method of the raw materials, where values of 525.09 μmol ET/g in jamaica, 554.92 μmol ET/g in mortiño, 561.35 μmol ET/g were obtained. in stevia and 19.22 μmol ET/g in aloe vera, these values obtained show that the raw materials are suitable for obtaining different products. For the antioxidant activity of the functional beverage rich in antioxidants sweetened with stevia, it was determined that treatment T1 presented an antioxidant activity of 5,597.01 μmol ET/1, this result obtained demonstrated superiority to the values reported by literature. In the sensory analysis carried out by a panel of semi-trained tasters, treatment T1 was selected as the best, since of the 5 attributes evaluated in 3 of them it was presented as the most scored, obtaining a rating of 4.23 in acceptability, which corresponds to the rating from Very Good to Excellent. The cost/benefit ratio was made to the best treatment which was T1, a utility of 25% was used which shows that the PVP of the final product for every 1,000 mL is $2.00, this price established when compared to other literature beverages presented a better price, which shows that the beverage obtained is more profitable and, above all, contains antioxidant and nutritional properties.